2009
DOI: 10.2527/jas.2008-1071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preslaughter withdrawal period on response of feedlot heifers to zilpaterol hydrochloride supplementation: Growth performance and carcass characteristics1

Abstract: Sixty-four crossbred heifers (451 +/- 23 kg) were used in a 42-d feeding trial (4 pens per treatment in a randomized complete block design) to evaluate the influence of preslaughter zilpaterol hydrochloride withdrawal period on growth performance and carcass characteristics. Heifers were fed a diet based on steam-flaked corn (2.13 Mcal of NE(m)/kg). Treatments were 1) control, no zilpaterol supplementation; 2) zilpaterol supplementation for 30 d, drug withdrawn from the diet 3 d preslaughter (ZIL-3); 3) zilpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
5
10
0
Order By: Relevance
“…These results agree with effects of ZH on fat deposition of finishing ewe lambs under heat stress (Macias-Cruz et al, 2010). In general, several studies in the literature in which effects of ZH were evaluated on deposition of internal fat in heifers and culled cows agree with the results of the present study Neill et al, 2009;Robles-Estrada et al, 2009a;Strydom and Smith, 2010). Zilpaterol is considered a repartitioning agent that primarily functions through an increase of protein deposition, whereas other composition factors such as moisture, fat, and ash seem to be minimally affected (Leheskaet al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…These results agree with effects of ZH on fat deposition of finishing ewe lambs under heat stress (Macias-Cruz et al, 2010). In general, several studies in the literature in which effects of ZH were evaluated on deposition of internal fat in heifers and culled cows agree with the results of the present study Neill et al, 2009;Robles-Estrada et al, 2009a;Strydom and Smith, 2010). Zilpaterol is considered a repartitioning agent that primarily functions through an increase of protein deposition, whereas other composition factors such as moisture, fat, and ash seem to be minimally affected (Leheskaet al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…When ZH was added to the GP program and compared to the CON carcasses, HCW, yield grade, and LM area were increased by 5%, 33%, and 18%, respectively. The increase in HCW is comparable to other studies Robles-Estrada et al, 2009;Rathmann et al, 2012); however, the increase in LM area and yield grade are much greater than these studies, which may be due to the combination of GP utilized in the COMBO treatment. Montgomery et al (2009) found that heifers supplemented ZH without being administered anabolic implants had only a 9% increase in LM area and yield grade when compared to heifers not subjected to GP technologies.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 79%
“…However, in this study, the higher proportion Z carcasses with fat score 2 (55% for Z30), compared with C carcasses (27%), suggest that zilpaterol may have had an effect on fat deposition in cull cows. Significant effects in this regard were reported by Vasconcelos et al (2008) and Robles-Estrada et al (2009) for young animals supplemented with zilpaterol, whereas Leheska et al (2009) found no differences in carcass fat percentage in treated and untreated steers and heifers. Numerically, lower values for trimmed fat (%) in the hindquarter of Z carcasses, compared with C carcasses, further suggested lower fat yields and were mirrored by significantly higher (P , 0.05) trimmed meat proportions in the hindquarter of Z carcasses.…”
Section: Discussionmentioning
confidence: 88%
“…Vasconcelos et al (2008) did not find any effect of duration of zilpaterol supplementation on muscle-related traits such as rib-eye area. Robles-Estrada et al (2009) reported a positive trend (P 5 0.11) towards trimmed meat proportions in zilpaterol-supplemented young feedlot steers.…”
Section: Discussionmentioning
confidence: 90%